PENINGKATAN HASIL BELAJAR PKN DENGAN MODEL EVERYONE IS TEACHER HERE DI KELAS V SD - Yusnita, Latifa; Taufina, Taufina; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to improve the student learning outcomes in the Civics learning  used Everyone Is Teacher Here. The type of research is PTK by using qualitative and quantitative approach. Subject of this research were teacher and students of V grades were 20. Research conducted in two cycles. The research procedure includes planning, implementation, observation, and reflection. The result of this research I to II cycle. (a) Lesson plan. The cycle of I was 67,9% increased to 100% in the II cycle. (b) Implementation, teacher’s activity of I cycle was 77,5% increased to 96,7%. Students activity of I cycle had averaged was 75% increased in the cycle was 95%. (c) The students learning outcomes in the I cycle was 74,0% increased to II cycle wa 85,6%.  Keywords: Learning outcome, PKn, Everyone is Teacher Here